The Balkans in the New Energy Architecture: Political Dynamics and Economic Challenges - Joneva, Elizabet (Research Papers, 2019)
In the last decades, the subject of the development of the energy sector in the Balkan countries provokes special attention due to its relevance in the context of the changing geopolitical and geoeconomic landscape in Eurasia, as well as the transformations on a global level. The aim of the study is to discuss the main dimensions of the significance of this region and the ambitions of the Balkans to act as a bridge between key energy zones.